Innovative systems for energy harvesting and storage - Caputo, Marco; Chiarello, Gennaro; Goldoni, Andrea; Carbone, Vincenzo (My University, 2014)
Energy harvesting represent one of the most important problem in today's society: climate changes and geopolitical instabilities remember ourself everyday the needs to nd alternatives to hydrocarbon exploiting. During my PhD period I concentrated my e orts in elaborating new scienti c knowledge to be applied to innovative energy harvesting and storage systems. Most of my work has been focused on the organic energy harvesting systems, like photoelectrochemical cells, solid-state organic photovoltaic cell, and hybrid organic-inorganic perovskites. Electronic structure and interface dynamics of macromolecules (poprhyrins, phthalocyanines, phenacenes, and fullerenes) have been investigated by mean of synchrotron radiation-based experimental techniques. Alternative systems for dye sensitized solar cell to the commonly used Ru-dyes/TiO2 interface were investigated, with encouraging results in the case of Zn-tetra phenyl poprhyrine/ZnO, while K doped picene/C60 interface exhibited properties with possible applications in the eld of superconductivity. Interface e ect have been found to cause also in hybrid organic-inorganic perovskites interesting long-living excitonic states, whose tailoring can lead to high e ciency devices. Doping and morphology e ects have been investigated for polymers and molecular thin lms. It was shown that nanoimprinting treatments can improve the PEDOT:PSS conductibility and in the meanwhile control the work function, both key parameters in an organic photovoltaic device, instead simply crystal packing in octaethyl porphyrins has found to be responsible for heavy electronic modi cations in the frontier orbitals. E orts were also made in nding new systems for energy storage. Innovative electrodes for lithium batteries were chemically characterized, while a study on the oxidation dynamic of metallic alloy usable in advanced fuel cells revealed interesting segregation dynamics.
Dipartimento di Fisica, Scuola di Dottorato "B: Telesio" Sistemi Complessi, Ciclo XXVII, a.a. 2014
Keywords: Struttura della materia; Energie rinnovabili